The Impact of Legal Reforms on Social Equity - Sudrajat, Arip Rahman; Urbaningrum, Rexy Nakula (Journal of Law and Social Politics, 2025)
Legal reforms play a critical role in shaping social equity by influencing access to justice, economic opportunities, and human rights protections. Historically, legal systems have both reinforced and dismantled systemic inequalities, depending on the nature and implementation of reforms. This study aims to analyze the impact of legal reforms on social equity, specifically focusing on how legislative changes affect marginalized communities. The research adopts a qualitative approach, employing a systematic literature review and comparative case studies from various jurisdictions to examine the effectiveness of legal reforms in reducing social disparities. The findings reveal that legal reforms have contributed to greater social equity in areas such as anti-discrimination policies, labor rights, and criminal justice. However, disparities persist due to inconsistent enforcement, socio-political resistance, and economic barriers. The study highlights that successful legal reforms integrate participatory governance, public accountability, and equitable enforcement mechanisms. Despite these advancements, challenges remain, particularly in ensuring that reforms are effectively implemented and do not inadvertently exacerbate existing inequalities. In conclusion, legal reforms serve as a crucial mechanism for fostering social equity, but their success depends on robust institutional frameworks and active civic engagement. This study contributes to the ongoing discourse on law and social justice by providing insights into best practices for designing and implementing legal reforms that promote equitable outcomes. Future research should explore the long-term socio-economic effects of legal reforms across different legal traditions.